Human iPS cell-engineered three-dimensional cardiac tissues perfused by capillary networks between host and graft - Hidetoshi Masumoto; Jun K. Yamashita (BMC, 2018)
Abstract Stem cell-based cardiac regenerative therapy is expected to be a promising strategy for the treatment of severe heart diseases. Pluripotent stem cells enabled us to reconstruct regenerated myocardium in injured hearts as an engineered tissue aiming for cardiac regeneration. To establish a long-term survival of transplanted three-dimensional (3D) engineered heart tissues in vivo, it is indispensable to induce microcapillaries into the engineered tissues after transplantation. Using temperature-responsive culture surface, we have developed pluripotent stem cell-derived cardiac tissue sheets including multiple cardiac cell lineages. The application of gelatin hydrogel microsphere between the cell sheet stacks enabled us to generate thick stacked cell sheets with functional vascular network in vivo. Another technology to generate 3D engineered cardiac tissues using cardiac cells and biomaterials also validated successful induction of vascular network originated from both host and graft-derived vascular cells.